Perancangan Papan Informasi Digital (Pindit) Berbasis Web Online Pada Jurusan Teknik Elektro Universitas Riau - Syachrodi Syachrodi; Salhazan Nasution (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2021)
Digital signage is a medium that used to inform the direct information and announcement faster, precisely, and up to date. On Electronics Engineering at the University of Riau, the medium that used to inform the information and announcement still use conventional methods, that is wall magazine and using social media WhatsApp. To maximize the information and announcement system, we design digital signage based on the online web that can be accessed via an internet connection. The result of this research is to get better information and announcement system on Electronics Engineering at the University of Riau. Not just that, the admin can manage all of the information that should be informed to academic civitas easily. The test method used in this research is the black box testing and the system build with framework CodeIgniter and MySQL database. Keywords: digital signage, raspberry pi, web, rfid, announcement